Oral delivery of Eimeria acervulina transfected sequentially with two copies of the VP2 gene induces immunity against infectious bursal disease virus in chickens - Guo, Qingbin; Yu, Ying; Suo, Jingxia; Tang, Xinming; Zhang, Sixin; Crouch, Colin; Bruton, Beth; Tarpey, Ian; Liu, Xianyong; Zhao, Guanghui; Suo, Xun (Frontiers in Veterinary Science, 2024)
Chicken coccidiosis caused by Eimeria spp. can occur on almost all poultry farms, causing huge economic losses to the industry. Genetically manipulated Eimeria parasites as a vaccine vector to deliver viral antigens have been reported. In our preliminary study, transgenic E. acervulina expressing a VP2 gene (Ea-VP2) of infectious bursal disease virus demonstrated partial protection against IBDV infection.To enhance immune responses, we aimed to increase the VP2 gene copy number in transgenic E. acervulina. In this study, we employed a novel plasmid vector carrying a VP2 gene fused with three flag tags and red fluorescent reporter gene (mCherry). The vector was introduced into Ea-VP2 sporozoites through nucleofection, leading to the generation of Ea-2VP2. Subsequent analysis revealed a notable escalation in the fluorescent rate, rising from 0.11% to 95.1% following four consecutive passages facilitated by fluorescent-activated cell sorting. Verification via PCR, western blot, and immunofluorescence confirmed successful construction of the Ea-2VP2 population.Despite lower fecundity compared to wild-type E. acervulina, Ea-2VP2 maintained immunogenicity. Our research effectively created a transgenic E. acervulina strain 2 transfected sequentially with two different copies of the VP2 gene from IBDV. This modification resulted in an increased humoral immune response after primary immunization in chickens. Additionally, it demonstrated a degree of protection within the bursa against IBDV infection. Future studies will focus on further enhancing the immune response levels.